The Supreme Administrative Court and the 2015–2019 reform of the judiciary – selected issues - Michalak, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
2015–2019 – the period of the first coalition rule under the leadership of the Law and Justice party (PiS) brought a number of legislative changes regarding the judiciary, or more broadly, the justice system. Beginning with a number of amendments and new laws adopted in 2015–2016 changing the organization and operation of the Constitutional Tribunal, the government also merged the offices of the Prosecutor General and the Minister of Justice, reformed the National Council of the Judiciary, introducing a new (and constitutionally questionable) procedure for appointing its members, and reformed the Supreme Court (establishing two new chambers). All changes raised and still raise doubts as to their compliance with the Polish Constitution and EU law. The purpose of this article is to summarize the rulings of the Supreme Administrative Court in matters resulting from the legislative changes introduced by the PiS government in 2015–2019. The publication takes into account the judgments of the Supreme Administrative Court issued until December 31, 2019 and discusses the position of the Supreme Administrative Court with regard to three issues: the right to demand – in the mode of access to public information – disclosure of lists of support of candidates for the newly appointed National Council of the Judiciary; the possibility of lodging appeals with the Supreme Administrative Court in individual cases concerning the appointment to the office of a judge of the Supreme Court, the power to adjudicate by a judge appointed at the request of the National Court Register in the current composition.